2016
DOI: 10.2147/ijn.s105348
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic radiosensitizing effect of tirapazamine-conjugated gold nanoparticles on human hepatoma HepG2 cells under X-ray irradiation

Abstract: Reductive drug-functionalized gold nanoparticles (AuNPs) have been proposed to enhance the damage of X-rays to cells through improving hydroxyl radical production by secondary electrons. In this work, polyethylene glycol-capped AuNPs were conjugated with tirapazamine (TPZ) moiety, and then thioctyl TPZ (TPZs)-modified AuNPs (TPZs-AuNPs) were synthesized. The TPZs-AuNPs were characterized by transmission electron microscopy, ultraviolet-visible spectra, dynamic light scattering, and inductively coupled plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…We found that AuNPs could significantly improve the hydroxyl radical production and the cell-killing effects of X-rays and fast carbon ions 12 . We also synthesized the reductive thioctyl tirapazamine (TPZs)-modified AuNPs (TPZs-AuNPs) and showed their ability for radiation enhancement 24 . We further proposed that ionizing radiation exposure was cell cycle phase-dependent for cellular uptake of gold nanoclusters (AuNCs).…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…We found that AuNPs could significantly improve the hydroxyl radical production and the cell-killing effects of X-rays and fast carbon ions 12 . We also synthesized the reductive thioctyl tirapazamine (TPZs)-modified AuNPs (TPZs-AuNPs) and showed their ability for radiation enhancement 24 . We further proposed that ionizing radiation exposure was cell cycle phase-dependent for cellular uptake of gold nanoclusters (AuNCs).…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…Our work has focused on the biological mechanisms of ionizing radiation, including the radiosensitizing mechanisms of nanoparticles. [23][24][25] The aim of the present study was to evaluate the radiosensitizing effects and mechanism of GONs in NSCLC cells under X-ray irradiation. After the cellular uptake and cell viability of GONs in NSCLC cells were studied, the clonogenic survival fractions of human NSCLC cells were investigated in the presence of GONs under X-ray irradiation compared to that of cells treated with irradiation alone.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to previous reports, in which similar TPZ–amide analogs were formed, we found that traditional carbodiimide‐ or uronium‐based coupling approaches produced numerous unidentified side products, which were impossible to remove with column chromatography . Alternatively, the use of acid anhydrides alone was not powerful enough to allow a reaction to take place.…”
Section: Resultsmentioning
confidence: 99%